DETERMINAN PERUBAHAN DESAIN OMAH MBOK MASE TERHADAP KARAKTER KAMPUNG LAWEYAN DI SURAKARTA - Hastuti, Dhian Lestari (Acintya, 2018)
This articleis the result of research about change design determination of Omah Mbok Mase To Character Kampung Batik Laweyan Surakarta Year 2004-2015. The research method is used phenomenology by using the Social Change Theory aproach. The result is the process of design changes Omah Mbok Mase caused by: 1) Fortress (front wall fence) built souvenir shop, 2) Tear down of buildings and replace with new buildings, 3) Selling of building structures 4) Sell all the assets, 5) Revitalize the building as a souvenir shop. The determinants of such design changes are influenced by internal factors, namely: the financial problems of the Omah Mbok Mase heirs, the inheritance system, and the mindset of trading that still using conventional means. External factors are the influence of technology and regulation of Surakarta City Government. Technological influences play a role in the cultural lag of process in economic activity. The Omah Mbok Mase heirs are evolving in a social change from a closed-character society to an open character, which must serve the tourists.Keywords: Determinant, design changes, Omah Mbok Mase, social changes, Laweyan